Analysis of the Mechanical Characteristics of the Basic WALK Step in Rumba from a Kinematic Perspective - Yu Wu (International Journal Bioautomation)
Objective: This study aims to explore the mechanical differences in executing the basic WALK step of the rumba from a kinematic perspective between professional dancers and amateur students, thereby guiding the teaching and training of the WALK step. Methods: Five professional dancers and five amateur students participated in video recordings using two JVC cameras. Kinematic data were processed using APAS software to analyze the center of gravity changes and lower limb joint data in both groups. Results: The movement time of the center of gravity showed no significant difference between the professional dancers and amateur students at different stages of the complete WALK step (p > 0.05). Center of gravity displacements were similar on the X-axis, but significant differences were observed on the Y and Z axes (p < 0.05). In lower limb kinematics, the amateur group exhibited notable variations in hip and knee flexion and extension in the sagittal plane compared to the professional group. Peak hip flexion and extension angles were 51.26 +/- 4.45° and -11.33 +/- 0.91°, respectively, in the amateur group, both smaller than those in the professional group (p < 0.05). Additionally, the peak knee adduction angle in the frontal plane was -4.64 +/- 5.65°, significantly smaller than that of the professional group (p < 0.05). The amateur group also demonstrated significant differences from the professional group in hip internal and external rotation, knee internal rotation, and ankle external rotation in the horizontal plane. Conclusion: The amateur group exhibits insufficient hip twisting and weak joint control during the execution of WALK steps, making them more susceptible to sports injuries. Strengthening lower limb muscle groups and improving overall body stability are recommended for this group.